The Use of Fun Activities in Enhancing the TeachingLearning English vocabulary at Middle school - SNOUSSI, Souaad (My University, 2017)
The aim of this study is to investigate to what extent Fun activities are effective in enhancingthe learning of English Vocabulary. The relevance of this study is linked to the fact that Fun activities are absent in our schools. To verify that, the methodology used in this research is based on a descriptive study, by collecting data from questionnaires addressed to both learners and Middle school teachers of fourth year middle school in Bouguirat-Mostaganem, as well as, from the observation and teacher’s interview. The results show that Fun activities have a good influence on the learner’s learning process, especially on vocabulary learning which help them to memorise new words easily in a short time memory. However, they need to be well selected by teachers, and should be used in the right time and with the appropriate conditions. Furthermore, Fun activities help in building a good relationship between teachers and learners, and between learners as well, so a good interaction will take place. The results obtained indicate that Fun activities play an important role on learner’s motivation, but we cannot always rely on them, in the sense that, there are different techniques to make the teaching learning easy.
The Case of Bouguirat “08 May 1945” Middle School
Keywords: Fun activities; Good interaction; Learners’ motivation